"We are Anonymous.": Anonymity in the Public Sphere – Challenges of Free and Open Communication (Global Media Journal - German Edition, 2013)
Anonymity, the stealth mode of public communication, challenges different actors who deal with freedom of communication issues in their day to day life – be it professional journalists, information and communication scientists, technicians or political activists. This article aims to deliver theoretical background on the concept of anonymity on the macro-level, as well as to shed light on how different communicators deal with anonymity on the micro-level. Based on the example of the Anonymous movement, communicative actions are put in relation to media technological artifacts and their surrounding media environment with a focus on journalistic practice and public response to the phenomenon. The analysis concludes with the need for a preservation of options for anonymous public communication as a dimension of freedom of communication after carefully considering both the advantages and the potential risks connected to that mode of private-public communication.
Keywords: anonymity; Anonymous; authorship; authenticity; accountability; credibility; freedom of communication; freedom of speech; journalism ethics; online communication; privacy